Non-Linear Modelling and Control of Permanent Magnet Synchronous Machine for Actuator Applications - Babu Bobba, Phaneendra; Vakil, Gaurang I; Gajala, Himavarsha; B V, Ravi Kumar (International Journal of Integrated Engineering, 2024)
Permanent magnet synchronous motors grabbed the attention due to their intrinsic characteristics. Aerospace applications necessitate great dependability and while reducing weight, complication, fuel intake, working expenses, and environmental effects. All these demands can be fulfilled to some extent with the PMSM motors because of their characteristics. The mathematical modelling of an Interior permanent magnet synchronous motor (IPMSM) including nonlinearities is proposed in this paper. The conventional models neglect nonlinearities such as hysteresis and eddy current losses, parameters variation with respect to rotor angle, magnetic saturation, cross-coupling effect, armature reaction, etc. The present model considers core loss and inductance varying concerning rotor position. Usually, the core loss is taken as a constant loss, but it varies with the speed. Ignoring the above parameters may deteriorate the performance of the motor in real-time compared to linear model. To validate the efficacy of the proposed model, two models are simulated in MATLAB and the results are compared.